The concept of the project of an interdisciplinary institution in limited universities - L. V. Adonina; T. A. Kokodey; E. A. Posnaya (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The article focuses on the formation of the concept of the project of an interdisciplinary institution in the structure of the university, since interdisciplinary connections contribute to the most eﬀective perception of the taught material and analysis of the current situation in the disciplines studied. Target. Based on various methods and techniques of analysis, determine the eﬀectiveness of developing the concept of interdisciplinarity in a university.Materials and methods. This study examines the possibilities for developing various types of interdisciplinarity in higher education. Methods of comparison, analysis and synthesis and others were used.Results and discussion. The concept of a project for an interdisciplinary institution in the university system, within the framework of cross-disciplinarity, is proposed, using the example of Sevastopol State University (SevSU). The goals, objectives and main directions of activity of the Center for Strategic Assessments and Forecasts of the Regional Education System on the basis of Northern State University have been determined.Conclusion. The necessity and importance of applying the concept of an interdisciplinary institution project in the structure of a university has been proven.